Genomic and Phenotypic Characterization of a Wild Medaka Population: Towards the Establishment of an Isogenic Population Genetic Resource in Fish. Issue 3 (1st March 2014) - Spivakov, Mikhail; Auer, Thomas O; Peravali, Ravindra; Dunham, Ian; Dolle, Dirk; Fujiyama, Asao; Toyoda, Atsushi; Aizu, Tomoyuki; Minakuchi, Yohei; Loosli, Felix; Naruse, Kiyoshi; Birney, Ewan; et al.
Abstract: Oryzias latipes (medaka) has been established as a vertebrate genetic model for more than a century and recently has been rediscovered outside its native Japan. The power of new sequencing methods now makes it possible to reinvigorate medaka genetics, in particular by establishing a near-isogenic panel derived from a single wild population. Here we characterize the genomes of wild medaka catches obtained from a single Southern Japanese population in Kiyosu as a precursor for the establishment of a near-isogenic panel of wild lines. The population is free of significant detrimental population structure and has advantageous linkage disequilibrium properties suitable for the establishment of the proposed panel. Analysis of morphometric traits in five representative inbred strains suggests phenotypic mapping will be feasible in the panel. In addition, high-throughput genome sequencing of these medaka strains confirms their evolutionary relationships on lines of geographic separation and provides further evidence that there has been little significant interbreeding between the Southern and Northern medaka population since the Southern/Northern population split. The sequence data suggest that the Southern Japanese medaka existed as a larger older population that went through a relatively recent bottleneck approximately 10, 000 years ago. In addition, we detect patterns of recent positive selection in the Southern population. These data indicate that the genetic structure of the Kiyosu medaka samples is suitable for the establishment of a vertebrate near-isogenic panel and therefore inbreeding of 200 lines based on this population has commenced. Progress of this project can be tracked at http://www.ebi.ac.uk/birney-srv/medaka-ref-panel .